1457Aboriginal and/or Torres Strait Islander deaths by suicide in Australia. (2nd September 2021) - Cutler, Tessa; Pirkis, Jane; Eades, Sandra; Gibberd, Alison; Gubhaju, Lina
Abstract: Background: The fifth leading cause of death for Aboriginal people in Australia is suicide. These deaths are preventable, and their impact is significant for family and the wider community. This work aims to increase understanding of suicide deaths among Aboriginal people by describing these deaths by a range of factors, and identifying similarities and differences between Aboriginal and non-Aboriginal deaths by suicide. Methods: Suicide deaths in Australia from 2001 to 2019 will be identified from the National Coronial Information System database. Demographic factors, details of the deaths and geographic factors will be described, and comparisons will be made between Aboriginal and non-Aboriginal deaths by suicide. Overall suicide rates by Aboriginal status and age- and sex-standardised rates per 100, 000 person-years will be calculated using mid-year estimated resident population and death counts stratified by year, age, sex, and Aboriginal status from the Australian Bureau of Statistics. Results: The analysis for this work is currently underway and will be finalised prior to the conference. Conclusions: The results of this research will provide information about sub-groups of the Aboriginal population and areas of Australia with heightened and reduced risks and rates of suicide. The findings will be interpreted with guidance from the Aboriginal Advisory Committee involved in this work. Findings will be shared with service providers, policymakers, communities, and researchers to enable improved targeting of interventions. Key messages: Better understanding of Aboriginal deaths by suicide is critical to inform and improve the much-needed targeting of services and interventions.